2017
DOI: 10.1200/jco.2017.35.15_suppl.e18227
|View full text |Cite
|
Sign up to set email alerts
|

Customized electronic alerts to boost pneumococcal vaccinations in high risk cancer patients.

Abstract: e18227 Background: Streptococcus pneumoniae remains a leading cause of serious illness, including bacteremia, meningitis, and pneumonia among adults in the United States. Approximately 10% of all patients with invasive pneumococcal disease die of their illness, but case-fatality rates are higher for immunocompromised adults including cancer patients. Current Center for Disease Control (CDC) guidelines recommend routine use of 13-valent (Prevnar 13) and 23-valent (Pneumovax 23) pneumococcal vaccines (PV) for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In total, 13 studies were analyzed for this review. [13][14][15][16][17][18][19][20][21][22][23][24][25]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 13 studies were analyzed for this review. [13][14][15][16][17][18][19][20][21][22][23][24][25]…”
Section: Resultsmentioning
confidence: 99%
“…17,21 One intervention involving electronic medical records built the influenza vaccine order into the admission order, 13 whereas another tied a best practice alert to the pneumococcal vaccine order set. 21 Another study at an oncology clinic placed an influenza vaccination prescription in patients' charts during their visit. Each of the five studies incorporated other interventions and each study saw a notable increase in vaccination rates.…”
Section: Studies Evaluating Interventions Targeted At Healthcare Workersmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have, for example, reported the need for more specific alerts specifying whether the PCV13 versus PPSV23 immunization is due to improve the chances that providers would act on CDS for children with kidney transplants. 30 Others have also developed immunization alerts for a specific medical condition 31 or to recommend the influenza immunization for children with CMCs 32 ; however, we are not aware of investigators who have developed an alert that encompasses multiple CMC-related immunizations and numerous CMCs.…”
Section: Discussionmentioning
confidence: 99%